Revelation of the IFNα, IL-10, IL-8 and IL-1β as promising biomarkers reflecting immuno-pathological mechanisms in porcine Huntington's disease model - Valekova, Ivona; Jarkovska, Karla; Kotrcova, Eva; Bucci, John; Ellederova, Zdenka; Juhas, Stefan; Motlik, Jan; Gadher, Suresh Jivan; Kovarova, Hana (Journal of neuroimmunology, 2016)
Studies on Huntington's disease (HD) demonstrated altered immune response in HD gene carriers. Using multiplexing immunoassay, we simultaneously investigated seven cytokines in secretomes of microglia and blood monocytes, cerebrospinal fluid (CSF) and serum collected from transgenic HD minipigs at pre-symptomatic disease stage. Decline in IFNα and IL-10 was observed in CSF and secretome of microglia whilst elevated IL-8 and IL-1β levels were secreted by microglia. Additionally, IL-8 was increased in serum. The proportion of mutant huntingtin in microglia may have causative impact on cytokine production. IFNα, IL-10, IL-8 and IL-1β represent promising biomarkers reflecting immuno-pathological mechanisms in porcine HD model.
Keywords: Immune response; kultivované buňky; DNA-Binding Proteins; Interleukin-1beta; Swine, Miniature; interferon alfa; cytokiny; Gene Expression Regulation; Lipopolysaccharides; Disease Models, Animal; proteiny vázající vápník; Central Nervous System; Porcine Huntington's disease model; interleukin-10; Cytokines; interleukin-8; Monocytes; mikroglie; Animals, Genetically Modified; Serum; miniaturní prasata; Interferon-alpha; Nerve Tissue Proteins; regulace genové exprese; monocyty; Cells, Cultured; Swine; interleukin-1beta; protein huntingtin; centrální nervový systém; Animals; modely nemocí na zvířatech; Central nervous system; Biomarker(s); zvířata; Humans; geneticky modifikovaná zvířata; biologické markery; lipopolysacharidy; mikrofilamentové proteiny; proteiny nervové tkáně; Calcium-Binding Proteins; Huntington Disease; Microglia; DNA vazebné proteiny; prasata; Biomarkers; Interleukin-10; Interleukin-8; Huntingtin Protein; Microfilament Proteins; lidé; Huntingtonova nemoc